Android Application Development based on 2D Animation Video on Cyber Bullying Crimes Related to Threatening and Grooming - Hamzah, Norhasyimah; Mohd Basri, Muhammad Hafiz; Zakaria, Normah; Rubani, Siti Nur Kamariah; Ariffin, Arihasnida (Research and Innovation in Technical and Vocational Education and Training, 2023)
The rapid development of technology brings many advantages and disadvantages to all levels of society. This study aims to design, develop, and evaluate the functionality of the development of an android application based on 2D animation video about cyberbullying crimes related to threats and grooming. This application serves to provide understanding and a fun experience to users because users can gain awareness of the crime of cyberbullying, threats, and grooming. This study is targeted at all levels of society so that they all know what the crime of bullying related to care and grooming is. ADDIE model used in this study involves five main phases, namely analysis phase, design phase, development phase, implementation phase and evaluation phase as well as the implementation of the development of this application using Adobe Animate 2020, Adobe Premiere Pro and Adobe Photoshop software and the overall findings of experts on this study can provide a high level of awareness among the community using 2D animation video. The experts to evaluate functionality of this study involved lecturers and teachers. The research instrument used is a checklist form. The results of expert’s research provide positive feedback on the use of this application and will help all levels of society to recognize cyberbullying-related crimes and grooming. In conclusion, the development of an android application based on 2D animation video on the crime of cyberbullying related to threats and grooming has many benefits that can be given to all levels of society.